Taṭbīq Ta’līm al-Imlā’ Al-Qāim ‘alā Lu’bah Takhmīn al-Kalimah liṭullāb al-Madrasah al-Ṡānawiyyah - Marliana, Imas; Fahrurrozi, Fahrurrozi (Study Program of Arabic Language Teaching, 2025)
This study aims to improve Imla’s learning outcomes in Arabic language classes by implementing a word-guessing game among seventh-grade students at SMP Swasta Muhammadiyah 48 Medan. This research employed a Classroom Action Research (CAR) method in two cycles. The primary data sources were the seventh-grade students and the Arabic language teacher. Data collection techniques included classroom observations, interviews with the teacher and students, and administering tests (pre-test and post-test) to measure students’ learning outcomes. The data were analyzed using qualitative descriptive techniques to interpret the results of observations and interviews, and quantitative analysis using a paired t-test to determine the significant differences between the pre-test and post-test results. The findings revealed a significant improvement in students’ learning achievements following the implementation of the word-guessing game, as reflected by the increase in average post-test scores compared to pre-test scores and statistically significant results from the t-test. Therefore, the word-guessing game proved effective in strengthening vocabulary mastery, enhancing Imla’s writing skills, and fostering student motivation and active participation in the learning process. This method is recommended as an innovative alternative for teaching Arabic at the junior high school level.